2020
DOI: 10.1136/injuryprev-2020-043767
|View full text |Cite
|
Sign up to set email alerts
|

Vacant lot to community garden conversion and crime in Milwaukee: a difference-in-differences analysis

Abstract: BackgroundVacant lots generate the perception of neglect and are often opportunistic locations for crime. Evidence is building to suggest that greening vacant lots, especially through community engaged approaches, is associated with reductions in some types of crime.MethodsUsing a retrospective quasi-experimental approach, we compared the conversion of vacant lots into community gardens (n=53) with a group of matched control lots (n=159) to examine the effect of this intervention on police reported theft, viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Greenspace quality, in this instance, refers to the level of greenness or diversity of vegetation, the maintenance of greenspace structures and amenities, as well as the inclusion of safety features such as lighting (Sadler et al, 2017). Experimental research has shown that improvements in the quality of these greenspaces, in fact, lowers crime (Beam et al, 2021). As Kimpton et al (2017, p. 304) note: ".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Greenspace quality, in this instance, refers to the level of greenness or diversity of vegetation, the maintenance of greenspace structures and amenities, as well as the inclusion of safety features such as lighting (Sadler et al, 2017). Experimental research has shown that improvements in the quality of these greenspaces, in fact, lowers crime (Beam et al, 2021). As Kimpton et al (2017, p. 304) note: ".…”
Section: Discussionmentioning
confidence: 99%
“…It then involves the development of physical designs that reduce the opportunity for crime to occur. While various localized 'greening' CPTED initiatives have been undertaken in the United States with reasonable success (see Beam et al, 2021;Branas et al, 2011;Kondo et al, 2016), there is a need for increased uptake of these initiatives nationally and, at least initially, in cities of greatest concern. Failure to do so may result in small, but impactful increases in violent crime for decades to come.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to improve conditions in disinvested, segregated neighborhoods to protect longterm residents from being displaced include the New Markets Tax Credit and the Healthy Food Financing Initiative. 76 In addition, turning vacant lots into community gardens or remediating abandoned houses may improve social cohesion and increase safety, [77][78][79] both of which are associated with CVD risk.…”
Section: Evaluating Policies and Interventions Aimed At Improving Nei...mentioning
confidence: 99%
“…Beam et al (2020) used quasi-experimental methods to study the impact of converting vacant lots into community gardens by comparing garden lots with planter boxes, benches, and small landscaping projects with unimproved control lots. Crime data were gathered from the municipal database and compared to imagery from satellite and ground data, and municipal records (Beam et al 2020). While theft was not affected, violent crime diminished (Beam et al 2020).…”
Section: Community Gardensmentioning
confidence: 99%
“…Crime data were gathered from the municipal database and compared to imagery from satellite and ground data, and municipal records (Beam et al 2020). While theft was not affected, violent crime diminished (Beam et al 2020). Focusing on community gardens' growth between 2005 and 2015, Koop-Monteiro (2021) gathered data on new community gardens, income, ethnic diversity, population, homeownership, and other demographic data and found that the addition of just one garden reduced property crimes (breaking and entering and vehicular theft).…”
Section: Community Gardensmentioning
confidence: 99%